EFFECTS OF WAVES ON DIFFERENT LAYERS (American Journal of Technology and Applied Sciences, 2024)
The mine was launched in 1935 and consists of 4 productive layers (horizons I, II, III, IV). . Futhermore a small amount of gas flow was obtained from the Upper Cretaceous Xenon layers from well No. 3. Drilling was carried out in the mine to determine the presence of oil and gas in Cretaceous and Jurassic period. In spite of the complex mining-geological structure of the region (AVPD), the attempts from the upper Cretaceous deposits, starting from the Turan Plateau, were unsuccessful. Nowadays, the mine is being used in the last stage. The depth of productive layers is 110-200 m.